2019
DOI: 10.3390/foods8100478
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Steeping Water Change during Malting on the Multi-Toxin Content in Malt

Abstract: The aim of this study was to assess the impact of steeping water change and Fusarium graminearum contamination level on different multi-toxin types and concentrations in barley malt. Malt samples were subjected to two micromalting regimes—steeping water change and the other with no steeping water change. Malt was contaminated with different F. graminearum contamination levels (0%, 10%, and 20%). The results indicate that malt with higher F. graminearum contamination levels ensured higher concentrations of toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Analogically, NIV-3G was in the range of 32-126% of NIV [28]. Similarly high DON-3G/DON values were described by Habschied et al, in barley malt, and depending on the method of malting and the level of F. graminearum infection, they obtained a relative content of DON-3G in the range of 45-82% [29]. Increased relative levels of DON-3G and NIV-3G metabolites have also been observed in many beer samples, which may confirm the high activity of glucosyltransferases during the malting process of grain, thus supporting the fact that there is secondary biosynthesis of DON-3G and NIV-3G [24,28,30,31].…”
Section: (A) (B)supporting
confidence: 79%
“…Analogically, NIV-3G was in the range of 32-126% of NIV [28]. Similarly high DON-3G/DON values were described by Habschied et al, in barley malt, and depending on the method of malting and the level of F. graminearum infection, they obtained a relative content of DON-3G in the range of 45-82% [29]. Increased relative levels of DON-3G and NIV-3G metabolites have also been observed in many beer samples, which may confirm the high activity of glucosyltransferases during the malting process of grain, thus supporting the fact that there is secondary biosynthesis of DON-3G and NIV-3G [24,28,30,31].…”
Section: (A) (B)supporting
confidence: 79%
“…This was also concluded by other researchers where levels were typically positively correlated with the amount of DON [44,47]. In Croatian wheat samples in the brewing industry, DON ranged from 595 µg/kg [48] to 2723 µg/kg in wheat malt [49], while concentrations in barley were considerably lower (up to 17.6 µg/kg) [50].…”
Section: Culmorin (Culm) 15-hydroxyculmorin and 5-hydroxyculmorinsupporting
confidence: 78%
“…Literature concerning dynamics of these processes is sparse. The following ratios have been reported: 22–186% for DON3G/DON and 32–126% for NIV3G/NIV in barley malt [ 36 ]; and 45–82% for DON3G/DON in barley malt (we have recalculated the data published by Habschied et al [ 37 ]). Bryła et al [ 19 ], Ksieniewicz-Woźniak et al [ 36 ], and Lancova et al [ 38 ] report that both DON3G/DON and NIV3G/NIV ratios found in numerus tested samples of beer were also higher than 100%.…”
Section: Resultsmentioning
confidence: 99%